Perancangan Desain Sistem Informasi Geografis Potensi Biogas Provinsi Lampung Menggunakan Aplikasi QGIS 3.34 - Wibowo, Widiyo; Isrolana, Isrolana; Merican, Marcellino Ricky; Pakpahan, Indah Sari Pariban; Sulaiman, Zainal Muttaqien; Meisyah, Ines Amelia; Febriani, Siti Diah Ayu (Jurnal Teknik Terapan, 2025)
Lampung, a province in Indonesia with a robust agricultural and livestock sector, exhibits substantial potential for biogas production. Biogas, derived from agricultural residues and animal manure, such as cow and goat dung, presents a sustainable alternative to conventional fossil fuels. Given the escalating global energy demand and environmental concerns, this study endeavors to quantify the biogas potential in Lampung, particularly focusing on the conversion of livestock manure into energy. Employing the QGIS application, this research maps the geographical distribution of biogas potential. Findings indicate that, with optimized management practices, Lampung could produce hundreds of thousands of tons of methane annually, sufficient to partially meet the energy requirements of local households and industries. Beyond energy generation, biogas production can stimulate economic growth, enhance farmers' incomes, and mitigate greenhouse gas emissions. However, the widespread adoption of biogas technology in Lampung is contingent upon addressing several challenges, including technological limitations, public awareness, and the need for conducive policy frameworks.